A comprehensive transcriptional reference for severity and progression in spinal cord injury reveals novel translational biomarker genes - Rubén Grillo-Risco; Marta R. Hidalgo; Beatriz Martínez-Rojas; Victoria Moreno-Manzano; Francisco García-García (Journal of Translational Medicine)
Abstract Spinal cord injury (SCI) is a devastating condition that leads to motor, sensory, and autonomic dysfunction. Current therapeutic options remain limited, emphasizing the need for a comprehensive understanding of the underlying SCI-associated molecular mechanisms. This study characterized distinct SCI phases and severities at the gene and functional levels, focusing on biomarker gene identification. Our approach involved a systematic review, individual transcriptomic analysis, gene meta-analysis, and functional characterization. We compiled a total of fourteen studies with 273 samples, leading to the identification of severity- and phase-specific biomarker genes that allow the precise classification of transcriptomic profiles. We investigated the potential transferability of severity-specific biomarkers and identified a twelve-gene signature that predicted injury prognosis from human blood samples. We also report the development of MetaSCI-app - an interactive web application designed for researchers - that allows the exploration and visualization of all generated results ( https://metasci-cbl.shinyapps.io/metaSCI ). Overall, we present a transcriptomic reference and provide a comprehensive framework for assessing SCI considering severity and time perspectives, all integrated into a user-friendly tool. Graphical abstract